Social Skill, Self-Efficacy and Pychological Wellbeing on High School Students - Fahmawati, Zaki Nur; Laili, Nurfi; Affandi, Ghozali Rusyid; Paryontri, Ramon Ananda (Universitas Muhammadiyah Metro, 2022)
Everyone must have psychological well-being, including high school students who experience various physical, cognitive, and emotional changes. Adolescents who cannot manage change correctly and adequately will take wrong actions and face mental health problems. This study examines the role of social skills and self-efficacy in psychological well-being. The subjects of this study were 774 high school students in Sidoarjo District. The sampling method used is cluster sampling. The results showed a positive relationship between self-efficacy and psychological well-being (rxy = 0.479; sig. <0.05). In addition, there is a positive relationship between social skills and psychological well-being (rxy = 0.523; sig. < 0.05). Self-efficacy and social skills can affect psychological well-being simultaneously (F = 179,348; sig. < 0.05). The magnitude of the influence of variables (self-efficacy and social skills) on welfare is 31.8%, and the assessment of other variables.